Insecticidal activity and sublethal effects of essential oils on Sitophilus zeamais (Coleoptera: Curculionidae) and on Acanthoscelides obtectus (Coleoptera: Chrysomelidae) - Ataide, Julielson Oliveira; Holtz, Filipe Garcia; Deolindo, Francieli Destefani; Huver, Andressa; Zago, Hugo Bolsoni; Menini, Luciano (Acta Biológica Paranaense, 2022)
The objective of this study was to evaluate the toxicity, the effects on the emergence and survival of the essential oils of Cymbopogon nardus, Corymbia citriodora and Cymbopogon martini and their mixtures, applied as fumigation, on Sytophilus zeamais and Acanthoscelides obtectus. The essential oil of C. nardus presented geraniol (38.93%) and citronellal (26.46%) as the main chemical compounds, C. citriodora presented citronelal (83.95%) and C. martini geraniol (85.67%). The essential oils and their mixtures showed mortality ranging from 3% to 16% on S. zeamais. However, on adults of A. obtectus they caused mortality ranging from 62.5% to 92.5%. The mixtures C. martini + C. citriodora and C. martini + C. nardus + C. citriodora caused 15% of emergence in adults of S. zeamais. The essential oil of C. martini decreased the survival of adults of S. zeamais in 20 days. The results showed that the essential oils and their mixtures caused toxicity and affected the emergence and survival of the adults of S. zeamais and A. obtectus. However, further studies are needed to improve essential oils to be used in the control of these stored grain pests.